Contributions of Robotics to the Safety and Efficacy of Invasive Monitoring With Stereoelectroencephalography - Faraji, Amir H.; Remick, Madison; Abel, Taylor J. (Frontiers in Neurology, 2020)
The purpose of this review is to provide a discussion of the history and utility of robotics in invasive monitoring for epilepsy surgery using stereoelectroencephalography (sEEG). The authors conducted a literature review of available sources to describe how the advent of surgical robotics has improved the efficacy and ease of performing sEEG surgery. The sEEG method integrates anatomic, electrographic, and clinical information to test hypotheses regarding the localization of the epileptogenic zone and has been used in Europe since the 1950s. One of the primary benefits of robot-assisted sEEG implantation techniques is the ability to seamlessly transition between both orthogonal and oblique trajectory types using a single technique. Based on available information, it is our view that when applied appropriately robotic sEEG has a relatively low rate of complications and many advantages over traditional craniotomy-based invasive monitoring methods.